Expanding the diagnostic spectrum of malignant otitis externa: a case report of proteus infection in a non-immunosuppressed patient - Arias Rodríguez, Fabián Darío; Larenas, Mercedes; Paredes, Santiago; Giuliano, Guillermina; López-Cortés, Andrés; Izquierdo-Condoy, Juan S. (Frontiers in Medicine, 2025)
IntroductionMalignant otitis externa (MOE) is a severe and potentially life-threatening infection of the external auditory canal, most frequently caused by Pseudomonas aeruginosa. Although typically seen in immunocompromised individuals—especially those with diabetes mellitus—up to 45% of cases have been reported in non-diabetic patients, highlighting the importance of recognizing atypical presentations. Rare pathogens, such as Proteus mirabilis, have been identified in only a few documented cases. Early diagnosis and prompt intervention are essential to prevent serious complications, including osteomyelitis and intracranial extension.ObjectivesThis report describes a really uncommon case of malignant otitis externa caused by P. mirabilis in a non-diabetic, immunocompetent patient.Case presentationA 53-year-old male with no relevant medical history presented with a four-month history of left-sided otorrhea, otalgia, and preauricular pain. Examination and imaging revealed purulent discharge and bone erosion, suggestive of MOE. Empirical treatment with amoxicillin/clavulanic acid was ineffective. Culture identified Proteus mirabilis, resistant to multiple antibiotics but sensitive to piperacillin/tazobactam, which was administered with supportive care. After 17 days of intravenous therapy, the patient improved and was discharged on oral ciprofloxacin to complete a three-month course. Follow-up confirmed clinical resolution without recurrence.ConclusionThis case report highlights an exceptionally rare occurrence of MEO caused by P. mirabilis in an immunocompetent, non-diabetic patient. It emphasizes the need to consider uncommon pathogens and atypical clinical profiles in MOE. Early diagnosis, microbiological confirmation, and tailored antimicrobial therapy were critical for favorable outcomes.